APLIKASI TEKNOLOGI PROSES RECYCLE AIR LIMBAH PADA USAHA DAUR ULANG PLASTIK DI DESA MARGO LESTARI JATI AGUNG LAMPUNG SELATAN - darni, yuli; Sulistiyanti, Sri Ratna (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2021)
The activity aims to improve and develop a partner in business unit to processing waste plastics to produce products with higher economic value. This activity gave impacts directly to attempt plastic waste disposal. The methods have done in this activity community service, covering socialization, training and application of using bed filter. In the socialization will be explained in a brief about the use and handling plastic waste. The training and application given to the partner business unit how about the use of a filter the type of bed filter. The activity was conducted in Desa Margo Lestari, Jati Agung, the targets are especially the partner of plastic waste management. The problem of the partner is the inefficient using water to wash the pieces of plastic. This directly affect needs of water and the quality product. In PKM activity, the managing partner of recycling plastic can be used bed filter to improve the efficiency of the amount of water to wash the pieces of plastic and to increase the economic profit of the partner.